Laboratory Model Test on The Sand Column for Reinforcement System of Flexible Pavement - Fajarwati, Yuli; Dian Eksana Wibowo; Endaryanta; Amalina, Anisa Nur (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2023)
Flexible pavement failures in Indonesia are primarily attributed to weak subgrade conditions, necessitating soil reinforcement measures. This study aimed to enhance soil-bearing capacity through soil reinforcement experiments utilizing a mixture of sand columns, rice husk ash, and cement. A prototype was constructed, including a 1×1×1 m steel box, an IWF steel frame, a dial gauge, a steel plate, and a proving ring, to apply a load to soil arranged within the iron box using a 3-ton hydraulic jack. The study focused on a clay soil type (following the AASHTO method) and conducted soil reinforcement in four scenarios. The result shows that in all scenarios involving a sand column, Scenario 1: 3% sand, 3% rice husk ash, and 6% cement obtained a qult is 0.23 kg/cm2 and BCR 114.94%; Scenario 2: 3% sand, 6% rice husk ash, and 3% cement obtained a qult is 0.12 kg/cm2 and BCR 11.49%; Scenario 3: 6% sand, 3% rice husk ash, and 3% cement obtained a qult is 0.14 kg/cm2 and BCR 26.44%; Scenario 4: 6% sand, 6% rice husk ash, and 0% cement obtained a qult is 0.24 kg/cm2 and a BCR of 116.09%. Notably, scenario 4, featuring a column composition of 6% sand, 6% rice husk ash, and 0% cement, achieved a significant increase in bearing capacity (qult) with a value of 0.24 kg/cm2 and a high Bearing Capacity Ratio (BCR) of 116.09%. Scenario 1 was the most effective in reducing moisture content by 4% relative to the original soil moisture content, with a mixture comprising 3% sand column, 3% rice husk ash, and 6% cement. The findings suggest that applying soil columns can enhance the performance of flexible pavements.